The Comparison of group and individual learning on academic performance of 3 rd year Medical Technology students on clinical microscopy experiments - Laude, Antonio F., Jr
In Medical Technology schools, experiments can be done individually or in groups to learn technical skills in the laboratory. The nature of student participation in group work and the effect of group work in experiments on cognitive competence, laboratory skills and attitudes of students have not been well-studied. The study compared the learning outcomes of different laboratory settings (individual work, working in groups of 3, and working in groups? of 6) in terms of knowledge, skills and attitudes toward learning, motivation to learn, responsibility, helpfulness, and teamwork. It also determined the students? perception of group work and individual work when performing laboratory experiments, and described the group dynamics while performing laboratory experiments when working in groups of groups 3 and 6. Using a randomized counter-balanced design, 36 third-year medical technology students were instructed to learn laboratory skills in three different settings: individual work, working in groups of 3 and working in groups of 6. They were rotated to these three learning settings in six experiments so that each student learned in two experiments under each setting. Written and performance examination, questionnaires and observational checklist was used for gathering data. The maximum written examination score in each experiment was 20. There is a significant difference of written examination scores of students. The scores were highest among those doing individual work (Mean = 15.2, SD = 2.18) compared to students working in groups of 3 (Mean =14.6, SD = 2.88) and students working in groups of 6 (Mean = 14.0, SD = 2.68). The maximum practical examination score in each experiment was 100. All students in the three settings passed the practical examination (Mean = 96.8, SD = 4.17). The mean rating for the attitude questionnaire responses involved 1= strongly agree, 2 = agree, 3= disagree, and 4 = strongly disagree. Attitudes of students in all three settings were favorable towards learning: individual work (Mean = 1.77, SD = .632), working in groups of 3 (Mean = 1.74, SD =.603), and working in groups of 6 (Mean = 1.76, SD = .599). Attitudes of students toward motivation to learn and responsibility were favorable: individual work (Mean = 1.78, SD = .613), working in groups of 3 (Mean = 1.78, SD =.598), and working in groups of 6 (Mean = 1.78, SD = .579). Also students working in groups gave a positive response to helpfulness and teamwork: working in groups of 3 (Mean = 1.89, SD = .61) and working in groups of 6 (Mean = 1.88, SD =.607). Students perceived that they learned better in a group but they perform the experiment better when doing individual work. When working in groups, students mainly performed the roles of performer of task, information/opinion giver and information/opinion seeker, and direction giver. They also actively listened and served as standard setter in the group. Students working in group of 3 had an average of 67 verbal exchanges with their group mates compared with an average of 33 verbal exchanges when they were working in group of 6. When students perform individual work, they tend to obtain high written examination scores than when they were assigned in groups. There is a significant difference on motivation and responsibility when performing individual work. Students have higher motivation when performing individual work than when working in groups. Students assume more responsibility when performing individual work than when working in groups. There is also a significant difference on the response toward ending up doing most of the work. When students perform individual work or working in groups of 3, they perceived ending up doing most of the work negatively, where they have positive perception when they worked in groups of 6. Students perceived group work as useful and they also perceived that they achieve better in examinations by learning in a group. Students prefer individual work and they also perceive that they perform better with individual work when doing laboratory experiments. Task function and maintenance roles are the similar among working in groups of 3 and 6. Students working in group of 3 interact more compared to groups of 6 members.